The Influence of Triclosan on the Thyroid Hormone System in Humans - A Systematic Review - Homburg, Mai; Rasmussen, Åse Krogh; Ramhøj, Louise; Feldt-Rasmussen, Ulla (Frontiers in Endocrinology, 2022)
Objectives Triclosan is an antibacterial agent suspected to disrupt the endocrine system. The aim of this study was to investigate the influence of triclosan on the human thyroid system through a systematic literature review of human studies. Methods Eligibility criteria and method of analysis were registered at Prospero (registration number: CRD42019120984) before a systematic search was conducted in Pubmed and Embase in October 2020. Seventeen articles were found eligible for inclusion. Thirteen studies were observational, while four had a triclosan intervention. Participants consisted of pregnant women in eight studies, of men and non-pregnant women in seven studies and of chord samples/newborns/children/adolescents in six studies. The outcomes were peripheral thyroid hormones and thyroid-stimulating hormone (TSH) in blood samples. Results Several studies found a negative association between triclosan and triiodothyronine and thyroxine, and a positive association with TSH; however, the opposite associations or no associations were also found. In general, the studies had limited measurement timepoints of thyroid outcomes, and the interventional studies used low concentrations of triclosan. Thus, study design limitations influence the quality of the dataset and it is not yet possible to conclude whether triclosan at current human exposure levels adversely affects the thyroid hormone system. Conclusions Further larger studies with more continuity and more elaborate outcome measurements of thyroid function are needed to clarify whether triclosan, at current exposure levels, affects the human thyroid hormone system.